1999
DOI: 10.1094/phyto.1999.89.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Recombination in Gibberella zeae

Abstract: We developed a method for inducing sexual outcrosses in the homothallic Ascomycete fungus Gibberella zeae (anamorph: Fusarium graminearum). Strains were marked with different nitrate nonutilizing (nit) mutations, and vegetative compatibility groups served as additional markers in some crosses. Strains with complementary nit mutations were cocultured on carrot agar plates. Ascospores from individual perithecia were plated on a minimal medium (MM) containing nitrate as the sole nitrogen source. Crosses between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
167
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(170 citation statements)
references
References 32 publications
0
167
3
Order By: Relevance
“…Similarity matrix generated through Jacquard coefficient. Bowden and Leslie (1999). They reported that sexual reproduction is considered as an important assumption for molecular divergence among the population from different geographical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarity matrix generated through Jacquard coefficient. Bowden and Leslie (1999). They reported that sexual reproduction is considered as an important assumption for molecular divergence among the population from different geographical regions.…”
Section: Discussionmentioning
confidence: 99%
“…This strain was derived from the same parental strain (CS3005) as the TRI5-GFP strain (see Table 1 for a summary of the fungal strains used in this study). Crossing was performed on carrot agar plates as described elsewhere (Bowden and Leslie, 1999). Ascospores were harvested from the Petri plate lid and spread on to ½ PDA plates containing 50 mg L -1 G418 and 200 mg L -1 hygromycin.…”
Section: Backcrossing and Genotypingmentioning
confidence: 99%
“…The F. graminearum wild-type strain, Z-3639 (Bowden & Leslie, 1999), and mutants derived from this strain were used in this study and are listed in Table 1. Conidial suspensions or agar blocks containing mycelia of each strain were stored in 20 % glycerol at 270 uC.…”
Section: Methodsmentioning
confidence: 99%